Evaluation of the environmental and human health impact of road construction activities. (20th January 2018) - Moretti, L.; Mandrone, V.; D'Andrea, A.; Caro, S.
Abstract: This work presents the results of the Life Cycle Assessment (LCA) of two different types of road cross-sections (i.e. embankment and trench sections) with the objective of calculating and analysing the environmental and human health impact related to their construction processes. The geometrical and technical characteristics of the examined sections comply with current Italian standards for minor highways. After analysing a base case scenario, the study evaluated the influence of several transportation conditions on the LCA of both cross-sections, including varying distances between quarries, landfills, mix plants and construction sites, and two European motorization types of road vehicles and earthmoving machines. In all cases, the LCAs included eight impact categories that were evaluated according to the European standard EN 15804. The results support the fact that several impact categories should be included as part of LCA studies if there is an interest for effectively mitigating the deleterious effects related to road construction. Indeed, the analyses show that the use of low impact procedures in the mix plants (e.g. reduction in mixing temperatures, increase of energy recycling), the renewing of the vehicle fleet, and the use of secondary raw materials provide better overall environmental results, not only in terms of greenhouse gas emissions but in all the impact categories considered.